PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) DAN IMPLEMENTASINYA DALAM RENCANA PEMBELAJARAN PAI MI - Zulaiha, Siti (BELAJEA: Jurnal Pendidikan Islam, 2016)
The activities ofteaching and learning often have no interference either from the self-learners or from external factors. To handle more acute disorder, then a teacher needs to consider a variety of methods and models that may be appropriate for the learners.Their concept of Contextual Teaching Learning (CTL) in the curriculum today is expected to answer these issues so that the teacherâs task to innovate into its application in the classroom in order to avoid disturbances in learning. Contextual learning (Contextual Teaching Learning) is a concept of learning that help teachers link between the material taught with real-world situations of students and encourage students to make connections between knowledge possesed by its application in their daily lives by involving seven major components of contextual learning, namely : constructivism, questioning, inquiry, learning community, modeling, and authentic assessment. Contextual learning can be applied to any subject or themes that fits with steps as well as its strategies. But in this paper, the author tries to give an example of the application of CTL on learning plan PAI (Aqidah Akhlak) of Islamic Elementary School (Madrasah Ibtidaiyah).